Kajian Status Kerusakan Tanahpada Lahan Pertanian di Kecamatan Denpasar - REDITYA A. S, BINTANG; SUYARTO, R.; KESUMADEWI, A. A. I. (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.5, No.1, Januari 2016, 2016)
ABSTRACT The Study of Soil Degradation at Agricultural Land In South Denpasar Sub-District Agricultural soil degradation is an important issue all over the world. This issue had gained attention by Indonesian Government as indicated by the released of Indonesian Government Regulation with serial Number of 150 on 2000 for prevention of agricultural soil degradation. Based on the regulation, a study was carried out to evaluate soil degradation on agricultural field of South Denpasar Sub-District o n February to July 2014. Observation area was selected based on work map that was developed by overlaying thematic maps, which were including landuse, soil and topography maps. The sampling locations were chosen according to Stratified Purposive Sampling method . The selected area were including rice fields that both located on Entisols and Inceptisols as well as dryland on Entisols that all of them laid down on slopeness ranging on 0-3%. The results of the study showed that agricultural field in South Denpasar Sub-District were potentially degraded on a range of very low – low.  Paddy field had potential degraded area that grouped to very low degraded, while dryland potentially low degraded. According to the matching and score methods based on the selected soil properties had been quantified, 26,48% of agricultural field in the research area considered to be low degraded with coverage area was 317,86 Ha of paddy field and another 73,52% (880 Ha of paddy field and 2,57 Ha of dryland) was undegraded. This findings was contradicted to their potential degradation. The soil degradation in paddy fields were indicated either by the soil permeability and electrical conductivity that were higher than that has allowed according to Indonesian Government Regulation. Keywords: Soil Degradation, Agricultural Land